Financial Performance Analysis of Andhra Bank - K. , Siva Nageswararao; Madhavi Latha, Challa; M. , Venkataramanaiah (International Journal of Psychosocial Rehabilitation, 2020)
The banking sector is the backbone of any economy. A bank acts as a catalyst to convert savings into investments so as to supply needy funds to the development of the economy in a county. The banking sector in India started flourishing in the 19th century with the arrival of Europeans in India. The beginning of the 19th century has witnessed the birth of many banks in India; Andhra Bank is considered one of the premier banks that came into existence to cater to the financial needs of the Telugu Region. After the independence of India, Andhra Bank has grown by leaps and bounds, and consequently the bank was nationalized in 1969. The study of the financial performance of the bank clues the readers in on how the bank is performing from several dimensions. With the help of the financial performance, one can understand how best the assets of the bank are utilized during the general course of its business affairs. At this juncture, an earnest attempt has been made by the researcher to analyze the financial performance of Andhra Bank in terms of its profitability and the factors that helped in improving the financial health of the bank. The results showed that there is a growth in the total earnings of the Andhra Bank during the study period. The growth is positively significant. The income derived from loans and advances may be more than that of the interest paid on them, including establishing charges. The working funds were utilized efficiently in the recent past when compared to the initial period of the study.